Nilai Moral dan Pendidikan dalam Novel Tanah Para Bandit karya Tere Liye - Arieska Rahma, Wanda; Pramujiono, Agung; Indayani (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the moral values and educational values in the novel Tanah Para Bandit by Tere Liye. Novels are complex stories and involve various problems. The novel Land of the Bandits by Tere Liye tells the story of Padma, a young woman who has been training physically, mentally, mentally and spiritually since childhood. He was trained by a grandfather named Abu Syik. This research approach uses a qualitative descriptive approach. The data source for this research is the novel Tanah Para Bandit by Tere Liye. The research data used is a choice of words, phrases and sentences that show aspects of moral values and education in the novel Tanah Para Bandit by Tere Liye. The data collection technique used by researchers to obtain data is in two stages, namely reading and taking notes. The data analysis technique used in the research uses interactive Miles and Huberman which consists of; data reduction, data presentation, and conclusions. The results of the research show thatthe moral values and educational values found in the novel Tanah Para Bandit by Tere Liye, namely moral values consisting of; moral values related to relationships with God, moral values related to relationships with other humans, and moral values related to relationships with oneself. The educational value found in this research consists of; honest, disciplined, hard working and independent.